Three essays on corporate finance - Ma, Yujing (2016)
In essay one, we present evidence that the desire to gain human capital is an important motive for corporate acquisitions. Our tests exploit the staggered recognition of the Inevitable Disclosure Doctrine by U.S. state courts, which prevents a firm’s employees from working for other competitors. We find a significant increase in the likelihood of being acquired for firms headquartered in states that recognize such doctrine relative to firms headquartered in states that do not. Heterogeneous treatment effects confirm the human capital channel: our result is stronger for firms with greater human capital, for firms with fewer tangible assets and for firms whose employees previously could switch jobs more easily.